2019
DOI: 10.1093/jac/dky564
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir plus lamivudine for initial treatment of HIV-1-infected participants with HIV-1 RNA <500 000 copies/mL: week 48 outcomes from ACTG 5353

Abstract: Background:The AIDS Clinical Trials Group study A5353 demonstrated the efficacy and safety of dolutegravir and lamivudine for initial treatment of HIV-1 infection at week 24 in individuals with HIV-1 RNA 1000-500 000 copies/mL. Optimal ART for treatment-naive individuals must be durable. Objectives:The aim of this study was to estimate the efficacy and safety of dolutegravir plus lamivudine at week 48 and compare the efficacy in participants with baseline HIV-1 RNA 100 000 copies/mL versus .100 000 copies/mL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The largest trial was a randomized controlled trial (GEMINI) that reported a non-inferior 91% virological response rate at week 48 for 716 persons receiving dolutegravir/lamivudine compared with a similar number of persons receiving dolutegravir plus tenofovir/emtricitabine 75 . The remaining two trials were pilot trials that enrolled 120 persons for 48 weeks (A5353) 20 , 77 or 20 persons for 48 weeks 76 . The VF rate was 10% in these two trials.…”
Section: Resultsmentioning
confidence: 99%
“…The largest trial was a randomized controlled trial (GEMINI) that reported a non-inferior 91% virological response rate at week 48 for 716 persons receiving dolutegravir/lamivudine compared with a similar number of persons receiving dolutegravir plus tenofovir/emtricitabine 75 . The remaining two trials were pilot trials that enrolled 120 persons for 48 weeks (A5353) 20 , 77 or 20 persons for 48 weeks 76 . The VF rate was 10% in these two trials.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst many studies have shown 2DRs are non-inferior to 3DRs for short-term virologic and immunologic endpoints, data comparing clinical endpoints remains scarce (11)(12)(13)(14)(15)(16)(17)(18)(19)37,38).…”
Section: Discussionmentioning
confidence: 99%
“…DTG/3TC: a switch to the two-drug combination DTG/3TC, a regimen shown to be effective as initial therapy, 81 was also recently shown to be non-inferior to continuing a TAF-based three-drug regimen in maintaining virologic suppression in HIV-1-infected ART-experienced adults. 82 This regimen may be considered for patients with significant metabolic comorbidities, such as cardiovascular, renal, or bone disease.…”
Section: Optimizing Antiretroviral Therapy In Setting Of Virologic Sumentioning
confidence: 99%